Why a ''New Testament''?: covenant as an impetus for new scripture in early Christianity - Baker, Levi S. (Text and editions for New Testament study, 2026)
"Why would early Christians perceive the need for a 'New Testament'? Unfortunately, most studies on the NT canon concentrate on its development and closing to the neglect of its impetus. Yet NT texts like 1 Tim. 5:18 and 2 Pet. 3:16 reveal that, within the first century, early Christians began receiving recent Christian texts as "Scripture", on par with their Old Testament scriptural collection. What explains this rapid and remarkable development? Levi Baker traces the connection between Scripture and covenant in early Judaism and early Christianity, arguing that the answer lies in early Christianity's conviction that Jesus had inaugurated the new covenant"-- Provided by publisher